2018
DOI: 10.1111/ane.12891
|View full text |Cite
|
Sign up to set email alerts
|

Pretherapeutic functional neuroimaging predicts tremor arrest after thalamotomy

Abstract: Our findings have clinical implications for predicting clinical response after SRS-T. Here, using pretherapeutic magnetic resonance imaging and data processing without prior hypothesis, we show that pretherapeutic network(s) interconnectivity strength predicts tremor arrest in drug-naïve ET, following stereotactic radiosurgical thalamotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
4
13
1
Order By: Relevance
“…This is in line with the results of most studies that showed tremor related alterations of the sensorimotor and cerebellar areas (Colebatch, 1990;Jenkins et al, 1993;Wills et al, 1995;Czarnecki et al, 2011;Fang et al, 2013;Mueller et al, 2017). Additionally, target connectivity to the aforementioned areas was associated with tremor improvement in VIM-DBS and ablative (thalamotomy) surgeries (Klein et al, 2012;Gibson et al, 2016;Akram et al, 2018;Middlebrooks et al, 2018;Tuleasca et al, 2018a).…”
Section: The Tremor Network and Pattern Of Beneficial Dbs Connectivitysupporting
confidence: 90%
“…This is in line with the results of most studies that showed tremor related alterations of the sensorimotor and cerebellar areas (Colebatch, 1990;Jenkins et al, 1993;Wills et al, 1995;Czarnecki et al, 2011;Fang et al, 2013;Mueller et al, 2017). Additionally, target connectivity to the aforementioned areas was associated with tremor improvement in VIM-DBS and ablative (thalamotomy) surgeries (Klein et al, 2012;Gibson et al, 2016;Akram et al, 2018;Middlebrooks et al, 2018;Tuleasca et al, 2018a).…”
Section: The Tremor Network and Pattern Of Beneficial Dbs Connectivitysupporting
confidence: 90%
“…Furthermore, we observed parts of the anterior DMN. In a recent report, we suggested that pretherapeutic IC between the anterior DMN and Brodmann's area 10 would be predictive of tremor arrest after SRS-T. 33 Moreover, in the same report, IC within another network, containing the bilateral thalamus and motor cerebellum lobule V, also found in the present analysis, was predictive of a decrease in tremor amplitude on the treated hand. 33 Lobule V is mainly associated with motor control.…”
Section: Figsupporting
confidence: 78%
“…In a recent report, we suggested that pretherapeutic IC between the anterior DMN and Brodmann's area 10 would be predictive of tremor arrest after SRS-T. 33 Moreover, in the same report, IC within another network, containing the bilateral thalamus and motor cerebellum lobule V, also found in the present analysis, was predictive of a decrease in tremor amplitude on the treated hand. 33 Lobule V is mainly associated with motor control. Furthermore, motor and somatosensory representations show largely overlapping activation patterns, with a major cluster focused in lobule V. 32 With regard to the SMA, it is interconnected with numerous structures by both efferent (including multiple basal ganglia structures such as the putamen, caudate, and ventrolateral and ventral anterior thalamus [targeted in our patients]) and afferent (basal ganglia [ventrolateral and anterior thalamus], insula, midbrain, etc.)…”
Section: Figsupporting
confidence: 78%
See 1 more Smart Citation
“…5,13,15 Vim radiosurgery (VimRS), as an alternative to standard stereotactic procedures, has 3 major limitations: indirect targeting, no intraoperative confirmation of the Vim target by electrophysiology, and a delayed clinical effect of up to 1 year after the procedure. 7,18,33,37 Tuleasca et al have proposed using resting-state functional MRI (fMRI), [30][31][32]34 a noninvasive neuroimaging technique that can be used to study spontaneous brain activity with minimal patient compliance, to study tremor pathophysiology and improve tremor arrest after VimRS, by using advanced computational techniques. 6 Resting fMRI measures functional connectivity, which has been classically defined as the temporal correlations between spatially remote, statistically independent neurophysiological events distributed across varying neuronal groups and areas.…”
Section: Imaging Techniquesmentioning
confidence: 99%